Patterns of aeolian deposition in subtropical Australia through the last glacial and deglacial periods. (July 2021) - Lewis, Richard J.; Tibby, John; Arnold, Lee J.; Gadd, Patricia; Jacobsen, Geraldine; Barr, Cameron; Negus, Peter M.; Mariani, Michela; Penny, Daniel; Chittleborough, David; Moss, Edward
Abstract: Debate about the nature of climate and the magnitude of ecological change across Australia during the last glacial maximum (LGM; 26.5–19 ka) persists despite considerable research into the late Pleistocene. This is partly due to a lack of detailed paleoenvironmental records and reliable chronological frameworks. Geochemical and geochronological analyses of a 60 ka sedimentary record from Brown Lake, subtropical Queensland, are presented and considered in the context of climate-controlled environmental change. Optically stimulated luminescence dating of dune crests adjacent to prominent wetlands across North Stradbroke Island (Minjerribah) returned a mean age of 119.9 ± 10.6 ka; indicating relative dune stability soon after formation in Marine Isotope Stage 5. Synthesis of wetland sediment geochemistry across the island was used to identify dust accumulation and applied as an aridification proxy over the last glacial-interglacial cycle. A positive trend of dust deposition from ca. 50 ka was found with highest influx occurring leading into the LGM. Complexities of comparing sedimentary records and the need for robust age models are highlighted with local variation influencing the accumulation of exogenic material. An inter-site comparison suggests enhanced moisture stress regionally during the last glaciation and throughout the LGM, returning to a more positive moisture balance ca. 8 ka.